SUATU PERSPEKTIF MEMBANGUN KAPASITAS RIIL PERGURUAN TINGGI BERBASIS MODAL INSANI - Ridwan Lutfiadi (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2004)
To maintain the efficacy of on an ongoing basi\, college need more and more many convergent the real capacitieses. Real capacities woke up around interest of competence eyre being based on capita! of humanity the interest extantness, motivation, and knowledge of aspiratif and of ethical all then- perpetrators. Capital potency can be multipied through the exploiting of technology\ and continue to be developed the intellect content of passing innovation. Considering college cannot exeed in various area, hence core competence require to be developed furthermore through cooperation between college which is synergic. To serve requirement all service users of college which is his order excelsior, is claimed high best service more and more his intellect content, so that real capacities of college need more focussed for the purpose of this.